Sentuh Tanahku Application: As Land Conflict Mitigation An Impact on Sustainable Environmental in Papua Selatan - Yusuf, Andi Patta; Haning, Mohamad Thahir; Ibrahim, Muhammad Akmal; Hasniati, Hasniati; Adam, Aenal Fuad (Department of State Administration - Musamus University, 2024)
Papua Selatan occur land conflicts are a very important matter because they arise from unclear ownership of land and use of natural resources. Sentuh Tanahku Application is a digital innovation to enhance the transparency and access to information on ownership and use of land. The research examines the Utilization of this application in the mitigation of land conflict while considering their implications for sustainable environmental development. This is a qualitative method type of research with a literature study approach which emphasizes secondary data as sources that can be analyzed through the use of NVivo software. The results and findings indicated that the